Always-on Culture dan Fear of Being Replaceable terhadap Burnout melalui Toxic Productivity serta Dampaknya pada Kepuasan Kerja Karyawan Generasi Z di Era Artificial Intelligence - Dinda Fadila Sari; Miswanto . (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2026)
The rapid advancement of Artificial Intelligence (AI), digital transformation, and flexible work arrangements has significantly reshaped organizational work practices. The widespread adoption of AI and digital technologies has accelerated the emergence of an always-on culture, in which employess are expected to remain constanly connected to worl beyond reguler working hours. Simultaneously, concerns about being replace by AI have intensified employees’fear of being replaceable, creating psychological pressure that may foster toxic productivity, increase burnout, and ultimately reduce job satisfaction, particulary among Generation Z employees, who represent the most technology-oriented workforce. This study aims to examine the effects of always-on culture and fear of being replaceable on toxic productivity, investigate the influence of toxic productivity on burnout and job satisfaction, and analyze the mediating roles of toxic productivity and burnout in the relationship between the independent variables and job satisfaction among Generation Z employees in the era of Artificial Intelligence. This study employed a quantitative explanatory research design using a survey method. The research population consisted of Generation Z employees in Indonesia who utilize digital technologies and Artificial Intelligence in their daily work activities. A total of 200 responden were selected through purposive sampling based on predetermined criteria, including being 18-27 years old, having at least six months of experience, and regulary using digital technology at work. Primary data were collected through an online questionnaire distributed via Google Forms using a five-point Likert scale. The data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with SmartPLS 4 software. The findings reveal that always-on culture and fear of being replaceable have positive and significant effects on toxic productivity. Furthermore, toxic productivity has a positive and significant effect on burnout and a negative and significant effect on job satisfaction. Burnout also negatively and significantly influences job satisfaction. In addition, both toxic productivity and burnout significantly mediate the relationships between always-on culture, fear of being replaceable, and job satisfaction. The findings indicate that excessive work connectivity and concerns about AI-driven job replacement reduce employees’job satisfaction by increasing toxic productivity by increasing toxic productivity and burnout. Therefore, organizations should foster healthier work environments by promoting work-life balance, supporting employees’ psychological well-being, and enhancing digital competencies to ensure that AI-driven workplace transformation improves productivity without compromising employee job satisfaction.